2020
DOI: 10.1002/admt.201901088
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Droplet Microfluidics Device Based on Integrated Soft Magnets and Fluidic Capacitor for Passive Extraction and Redispersion of Functionalized Magnetic Particles

Abstract: Based on a recent droplet microfluidic device for target molecules' extraction, purification, and redispersion, here an original fluidic control system is proposed to improve the device versatility and usability. This approach relies on the coupling of functionalized magnetic particles handling by integrated soft magnets and a passive droplet splitting control at a channel junction. To reach the high standards required for bioassays' implementation, this device integrates a pressure‐driven variable volume comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…However, during the process of supplying a blood sample into a microfluidic device, the syringe pump causes fluidic instability at low flow rates [22]. To stabilize unstable flows resulting from the syringe pump, several techniques including air cavity in a driving syringe [23] or microfluidic channel [24,25], portable air cavity unit [22,26], and flexible compliance unit [27][28][29][30][31][32], were demonstrated in microfluidic systems. These methods act on the compliance element in the fluidic circuit model.…”
Section: Introductionmentioning
confidence: 99%
“…However, during the process of supplying a blood sample into a microfluidic device, the syringe pump causes fluidic instability at low flow rates [22]. To stabilize unstable flows resulting from the syringe pump, several techniques including air cavity in a driving syringe [23] or microfluidic channel [24,25], portable air cavity unit [22,26], and flexible compliance unit [27][28][29][30][31][32], were demonstrated in microfluidic systems. These methods act on the compliance element in the fluidic circuit model.…”
Section: Introductionmentioning
confidence: 99%
“…Composite PDMS structures were also recently implemented on the channel wall for droplet microfluidic. Serra et al reported a device for the extraction, purification, and redispersion of target molecules by coupling soft composite magnets and passive fluidics [65]. Composite blocks were obtained by mixing iron particles (1 to 6 µm) with PDMS and pouring the mixture into a CycloOlefin copolymer master.…”
Section: High Concentrated Pdms Compositesmentioning
confidence: 99%
“…Microdroplets containing magnetic particles are always manipulated by permanent magnets or electromagnets on the plates covered by Teflon AF or other hydrophobic materials. Researchers have demonstrated the physical control mode of microdroplet motion and action based on magnetic particles and explored the intervention and extraction process of magnetic particles from microdroplets [33][34][35]. For example, Z.…”
Section: Magnetic Particlesmentioning
confidence: 99%